2022
DOI: 10.2478/cjf-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Knowledge and Perception about Fresh Fish from Organic Farming in Croatia

Abstract: Along with growing consumer awareness about the impact of food on health, there is a trend towards increasing fresh fish consumption. At the same time, the demand for organic food is increasing in the modern market. Although fruits, vegetables and nuts have the biggest share in the organic food market in Europe, the aquaculture production of organic fish is also growing. Therefore, the main aim of this study is to explore the knowledge and perception of Croatian consumers about fresh fish from organic farming.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…The highest interest in eco-labels was demonstrated in Cluster 1, which suggests that this segment of consumers not only have the strongest desire to consume farmed fish, but they are also highly sensitive to ecological and environmental features when buying fish. A recent study conducted in Croatia, however, revealed that only half of the study participants are willing to pay a higher price for fresh fish with an organic label, and half of them are even unaware of the possibility to buy such fish [ 30 ]. This points out the need for better communication with and education of consumers as to what a sustainable eco-label is [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest interest in eco-labels was demonstrated in Cluster 1, which suggests that this segment of consumers not only have the strongest desire to consume farmed fish, but they are also highly sensitive to ecological and environmental features when buying fish. A recent study conducted in Croatia, however, revealed that only half of the study participants are willing to pay a higher price for fresh fish with an organic label, and half of them are even unaware of the possibility to buy such fish [ 30 ]. This points out the need for better communication with and education of consumers as to what a sustainable eco-label is [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, only a few studies have investigated fish consumption in Croatia [ 27 , 28 , 29 , 30 ] and only one study has focused on farmed fish, examining consumer knowledge and perception about fish from organic aquaculture [ 30 ]. In view of the above, the aim of this study is to identify segments of Croatian fishery consumers based on their intention to consume marine farmed fish and to detect similarities and differences among these segments according to their sociodemographic characteristics, fish consumption habits and preferences in at-home and away-from-home occasions, beliefs about wild and farmed fish, knowledge about fish, usual place of purchase, and sources from which they obtain information about products.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that Croatian consumers are not knowledgeable about fresh organic fish. Only half of the study participants are aware of the possibility of buying fish from organic aquaculture in Croatia, and half of them are willing to pay a premium price for the fresh fish with this label [56]. Eco-labelled fish has a relatively higher price, and when considering the existing dissatisfaction of Croatian consumers with the price of fish, it is questionable whether eco-labelled products in Croatia could reach a larger group of consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The above biocides have certain limitations, including a potential danger to people or the environment, pesticide residues, and inferior food quality. Accordingly, research and development of safe and effective sterilization methods for aquatic products have aroused extensive attention [ 7 ].…”
Section: Introductionmentioning
confidence: 99%